Efficiency and incidence of taxation with free entry and love-of-variety - Kory Kroft; Jean-William Laliberté; René Leal Vizcaíno; Matthew J. Notowidigdo (Banco de México, 2023)
We develop a theory of commodity taxation featuring imperfect competition along with love-of-variety preferences and endogenous firm entry and exit, and we derive new formulas for the efficiency and pass-through of specific and ad valorem taxes. These formulas unify existing canonical ones and feature a new term capturing the effect of variety on consumer surplus. Intuitively, if taxes reduce product varieties in the market, then the impact on social welfare depends on how much consumers value variety. As a proof-of-concept, we use the theoretical formulas to identify love-ofvariety preferences in an empirical application. Our welfare analysis shows that the marginal excess burden of taxation is very sensitive to the estimated love-of-variety, which can overturn classical results on the desirability of ad valorem versus specific taxation
Keywords: H20; H22; H71; 330; Public Economics; Taxation; Tax Incidence; Sales Tax